Preliminary design of an automatic cooling system using solar photovoltaic (PV) system / Mohd Fahim Ilias - Ilias, Mohd Fahim (2010)
Automatic cooling system using solar photovoltaic system is a system that uses solar photovoltaic system as a source of electricity to generate the cooling system with the presence of controller to make the system to operate automatically. The aim of the project is to design the automatic cooling system inside car cabin. The purpose of the system is not for cooling the car cabin like an air conditioning system, but to reduce the temperature inside the car cabin when the car is being exposed to the hot sun. Temperature sensors detect the temperature inside and outside of the car and act as the input signal for the PIC (Programmable Interface Controller) microcontroller. PIC is used to control the system to operate automatically when the temperature inside car cabin above than the ambient temperature outside of the car. This project encompasses some literature review on the solar photovoltaic system and the ventilation inside car, sizing the PV system in order to determine the size of the PV module and the rechargeable battery to ensure the solar PV system operate efficiently with optimal costs, and also involves designing the automatic cooling system that provides ventilation inside car cabin by using solar photovoltaic energy as the source of electricity , fabricating the design to ensure the system function as desired, and testing to see whether it can reduce interior car temperature or not by installing the system into a car.